The Powers of Self-Reflection in English Language Learning Using Video Project Based-Learning - Sulistyo, Teguh; Lutviana, Rizky (Jurnal Pendidikan Bahasa dan Sastra, 2024)
Project based-learning (PjBL), focusing on students’ creativities in producing a particular task, has been variously integrated into English as a Foreign Language (EFL) instruction to promote students’ skills. To support PjBL, teachers have integrated the use of technologies in the classroom since technologies enable teachers to modify teaching-learning activities. One of the modes of technology commonly applied is video project-based learning (VPBL) due to its benefits for both teachers and students. Research reveals the benefits of integrating PjBL and VPBL by focusing on the learning outcomes. In addition, self-reflection, as the ability of students to assess themselves regarding how and what they have learned and done in the tasks, might empower students to be better. This study highlights the benefits of self-reflection in English language learning through VPBL. VPBL empowers learners to create videos on topics of interest, using English as the communication medium. This study is a kind of literature research summarizing the findings of the previous studies on the utilization of self-reflection on students’ speaking projects. The study found that VPBL fosters self-reflection among learners, as they must plan, produce, and evaluate their work. Self-reflection is a crucial skill for language learning, as it helps learners to identify their strengths and weaknesses, set goals, and monitor their progress. The powers of self-reflection in English language learning using VPBL indicate that teachers must employ such cases in the classrooms.